A Deep Dive into NoSQL Databases: The Use Cases and Applications - Raj, Pethuru; Deka, Ganesh Chandra (Advances in computers, 2018)
A Deep Dive into NoSQL Databases: The Use Cases and Applications, Volume 109, the latest release in the Advances in Computers series first published in 1960, presents detailed coverage of innovations in computer hardware, software, theory, design and applications. In addition, it provides contributors with a medium in which they can explore their subjects in greater depth and breadth. This update includes sections on NoSQL and NewSQL databases for big data analytics and distributed computing, NewSQL databases and scalable in-memory analytics, NoSQL web crawler application, NoSQL Security, a Comparative Study of different In-Memory (No/New)SQL Databases, NoSQL Hands On-4 NoSQLs, the Hadoop Ecosystem, and more.Provides a very comprehensive, yet compact, book on the popular domain of NoSQL databases for IT professionals, practitioners and professorsArticulates and accentuates big data analytics and how it gets simplified and streamlined by NoSQL database systemsSets a stimulating foundation with all the relevant details for NoSQL database researchers, developers and administrators